2013
DOI: 10.1596/1813-9450-6545
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Effects of Vocational Training: Constraints on Women and Drop-Out Behavior

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 38 publications
5
64
0
Order By: Relevance
“…Recently, three randomized evaluations have been conducted of vocational training programs directed at disadvantaged youth in Colombia (Attanasio et al, 2011), the Dominican Republic (Card et al, 2011), and Malawi (Cho et al, 2013). The results in Malawi and the Dominican Republic are consistent with the earlier literature, with no impact on employment in either, and perhaps modest increases in income in the Dominican Republic.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Recently, three randomized evaluations have been conducted of vocational training programs directed at disadvantaged youth in Colombia (Attanasio et al, 2011), the Dominican Republic (Card et al, 2011), and Malawi (Cho et al, 2013). The results in Malawi and the Dominican Republic are consistent with the earlier literature, with no impact on employment in either, and perhaps modest increases in income in the Dominican Republic.…”
Section: Introductionsupporting
confidence: 72%
“…9 Three months is the same as the average length of the classroom components in both the Colombian and Dominican Republic training evaluations (Attanasio et al, 2011;Card et al, 2011), although those programs also supplemented this with two to three month internships to provide further on-the-job training, and is also as long as the apprenticeship program to teach vocational skills in the Malawi study (Cho et al, 2013).…”
Section: Selection Of Evaluation Coursesmentioning
confidence: 99%
“…Buvinic and Furst-Nichols (2014) programs that delivered a mixture of skills training and job placement services to women in developing countries to positive effect. In contrast, Cho et al (2013) find that a vocational training program in Malawi failed to improve labor market outcomes for young women. The authors argue that program dropout driven by household and family obligations may have limited the efficacy of the program.…”
Section: Policy Focus: Job Matching Services and Vocational Trainingmentioning
confidence: 74%
“…This approach of bestowing unconditional grants contrasts with the normal approach of seeking to assess whether a grant given for a specific activity has the desired effect, as with ongoing studies of apprenticeship training in Kenya and Malawi, Francis Teal | Are apprenticeships beneficial in sub-Saharan Africa? which implicitly seek to assess the effect of subsidizing training [12], [13]. Although the studies are at too early a stage to show longer-term results, the Malawi study has concluded that training has improved the skills and self-reported well-being of participants, especially men, despite having no positive labor market outcomes in the short term.…”
Section: Limitations and Gapsmentioning
confidence: 99%